Co-Design in co-production processes: jointly articulating and appropriating infrastructuring and commoning with civil servants. Issue 3 (3rd July 2017) - Seravalli, Anna; Agger Eriksen, Mette; Hillgren, Per-Anders
Abstract: The public sector, increasingly acknowledging a need for change but strongly influenced by market logics, is experimenting with new forms of co-production of public services based on collaborations between public providers, citizens and societal actors. At the same time, Co-design researchers, are using approaches of infrastructuring and commoning to navigate questions of participation and collaboration in co-production. By discussing the case of ReTuren, a co-produced service for waste handling and prevention, this article presents how infrastructuring and commoning can offer guidance to civil servants engaging in co-production. In the case, civil servants on an operational level and an 'embedded' Co-Design researcher worked side-by-side in the co-production of the service, jointly articulating and appropriating approaches of infrastructuring and commoning. The case reveals that the joint appropriation and articulation of these Co-Design approaches can lead to the development of new ways of operating and perspectives in the public sector. However, it also highlights that this joint effort needs to involve people across organisational levels in order to minimise possible contextual and worldview breakdowns within public organisations.